2018
DOI: 10.1680/jgein.18.00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber reinforcement on shear strength and void ratio of soft clay

Abstract: In this study, a series of multi-stage drained reverse direct shear tests were carried out on soft clay samples reinforced with 0.25% and 0.50% polypropylene fibers of 6 mm, 10 mm and 19 mm in length. Tests were carried out at different normal effective stresses and cumulative horizontal shear displacement of 1.17 times of the sample width. Results showed an increase of the shear strength with the increase of fiber content and length. However, the rate of improvement was capped with the normal effective stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 63 publications
5
29
0
Order By: Relevance
“…Also, for PP waste fiber-reinforced sand at 1% usage, the peak strength was reached to 1614 kPa (about 7 times of the unreinforced one) at the same confining pressure. A similar trend was observed in previous works [4,[12][13]20]. As the plastic waste reinforced sand was subjected to deformation, friction which is appeared between soil and plastic wastes led to development of tensile stress in the plastic wastes, also increase in confinement of the sample, and consequently increase in the shear strength of the samples.…”
Section: Effect On Peak Strengthsupporting
confidence: 87%
See 3 more Smart Citations
“…Also, for PP waste fiber-reinforced sand at 1% usage, the peak strength was reached to 1614 kPa (about 7 times of the unreinforced one) at the same confining pressure. A similar trend was observed in previous works [4,[12][13]20]. As the plastic waste reinforced sand was subjected to deformation, friction which is appeared between soil and plastic wastes led to development of tensile stress in the plastic wastes, also increase in confinement of the sample, and consequently increase in the shear strength of the samples.…”
Section: Effect On Peak Strengthsupporting
confidence: 87%
“…Actually, the value of increase in peak shear stress for the sand reinforced with 15 mm length PET fibers is almost the same as that for the sand reinforced with 10 mm length fibers with a negligible difference. Previous research has also indicated a similar trend between the shear strength improvement of fiber-reinforced soil and the length of the fiber [4]. This phenomenon can be attributed to the following reasons:…”
Section: Effect On Peak Strengthsupporting
confidence: 68%
See 2 more Smart Citations
“…Meanwhile, many scientific research developments have been achieved in backfill mining technology, backfill materials, and the mechanical properties of backfills [6][7][8][9][10][11]. For example, Mirzababaei et al [12][13][14] studied the behavior of soft clay reinforced with short fibers, and found sand ratio of the backfill body, the changing range of the average infrared radiation temperature (AIRT) of the backfill body became increasingly smaller [26][27][28]. Cai et al found that the strength of pillars or rock masses surrounded by backfill material can increase [29,30].…”
Section: Introductionmentioning
confidence: 99%